Analysis and correction of diets of overweight and obese women - Babienko, Volodymyr; Shanyhin, Anton; Rozhnova, Anastasiia; Korkhova, Arina (Journal of Education, Health and Sport, 2023)
The proposed study is important and relevant in view of the increasing level of obesity in the world. Preventive interventions are important to reduce long-term health care costs and improve overall population health as health care systems struggle with the financial burden of obesity-related diseases. Hypodynamia and obesity act as predictors of the development of atherosclerosis and metabolic syndrome. It is worth noting that the level of vitamin D in blood serum affects the development of the risk factors listed above. Research results demonstrate an inverse relationship between the level of 25-hydroxyvitamin D in blood serum and the development of obesity, metabolic syndrome, and insulin resistance. As part of a prospective randomized controlled trial, 106 women aged 19 to 68 years (mean age 43.66±5.02 years) who had a BMI of 25 kg/m2 or higher were examined. Measures (weight, body mass index, 25(OH)D) were assessed at the start of the study and every four weeks to monitor development and dietary compliance for 6 months. After six months of individual dietary adjustments, body weight and BMI were significantly reduced. Participants reduced their weight on average by 7.13±0.78 kg and 2.53±0.19 kg/m2 (p<0.001). Individualized dietary adjustments resulted in significant weight loss, highlighting the value of individualized dietary interventions for effective weight management. A link between excess body weight and vitamin D deficiency has been established.